Gang ecological diversity in the Hollenbeck Area of Los Angeles, 1978-2012 - Brantingham, P. Jeffrey (The Oxford handbook of gangs and society, 2024)
Criminal street gangs are paradoxically both ephemeral and durable social forms. Unique gangs might emerge to only disappear a short while later, while others may persist for decades. These dynamics raise questions about the ecological diversity of gangs over time and space. This chapter examines gang diversity in an area of Los Angeles over a 35-year period. It looks to annual counts of the number of uniquely named gang cliques identified in gang-related homicides. The chapter finds that gang diversity fluctuates over time from a minimum of 8 to a maximum of 34 unique cliques. Homicide is concentrated among a small number of unique cliques; one uniquely named clique is tied to 86 homicides over this period. Most cliques are around for a very short period of time—the median lifespan of a clique is seven years, and 41% of all cliques appear for just one year. While the homicides per clique is relatively stable over time, it is clear that more cliques on the landscape is associated with more homicides per clique; there were 63% more homicides with 34 unique cliques on the ground compared to when there were just 4. Overall, the chapter estimates that this area of Los Angeles could support as many as 40 unique cliques at any one time. It considers several explanations for the observed patterns and discuss how gang diversity offers a unique window into the challenges communities with chronic gang problems face.